Pengaruh Promosi, Pelayanan dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan PT. Sakura Jaya Solusi - Sumarni Sumarni; Andik Rusdi D. (Fakultas Ekonomi Universitas Borobudur, 2021)
Customer loyalty is a top priority in this study because the level is getting sharper amongservice companies in Indonesia. the main thing is that the company can survive, compete anddominate the market, promotion and service quality must be improved. Service companies mustpay attention to the things that are considered important by customers. So that customers feelsatisfied and do not switch to other companies that are similar or their substitutes. So this studyaims to determine the effect of promotion, service quality and customer satisfaction and its impacton customer loyalty at PT. Sakura Jaya Solusi.The data used in this study are primary data collected from questionnaires that have beendistributed and filled out by customers. Methods of data processing using the method of pathanalysis (Path Analysis) with the help of analysis tools SPSS Version 20.0.The results showed simultaneously the promotion variable, service quality and customersatisfaction had a positive and significant effect on customer loyalty. Partially shows that there isa positive and significant effect between promotion on customer satisfaction. There is a positiveand significant influence between service quality on customer satisfaction. There is a positive andsignificant influence between promotion on customer loyalty. There is a positive and significantinfluence between service quality on customer loyalty.Keywords: Effect of Promotion, Service, Customer Satisfaction, and Customer loyalty